Eating Disorders and Homeopathy: An Integrative Approach - Sharma, Shivani (Indian Journal of Integrative Medicine, 2025)
Eating disorders are a group of psychiatric conditions characterised by abnormal eating behaviours causing significant distress or concern about body weight or shape. These disorders include anorexia nervosa, bulimia nervosa, binge-eating disorder, and other specified feeding and eating disorders (OSFED). Eating disorders affect both physical and psychological health, leading to severe emotional distress and psychiatric comorbidities such as depression and anxiety. While conventional treatment often includes psychotherapy, nutritional counselling, and pharmacological interventions, homoeopathy offers a complementary approach by addressing the individual holistically. This article explores the types, prevalence, psychological effects, and treatment approaches for eating disorders, emphasising the potential role of homoeopathy in integrative care. Evidence-based research, case studies, and the application of specific homoeopathic remedies in managing eating disorders are reviewed.